2014
DOI: 10.1016/j.conbuildmat.2014.09.091
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis frameworks for mechanistic-empirical pavement design of continuously reinforced concrete pavements

Abstract: The new AASHTO Mechanistic-Empirical Pavement Design Guide (MEPDG) performance predictions for the anticipated climatic and traffic conditions depend on the values of the numerous input parameters that characterize the pavement materials, layers, design features, and condition. This paper proposes comprehensive local sensitivity analyses (LSA) and global sensitivity analyses (GSA) methodologies to evaluate continuously reinforced concrete pavement (CRCP) performance predictions with MEPDG inputs under various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Kavussi et al (2014) utilized RSM to evaluate the effects of aggregate gradation, hydrated lime and Sasobit content on the indirect tensile strength of warm mix asphalt. Ceylan et al (2014) employed RSM to model the Global Sensitivity Analyses (GSA) results for evaluation of Mechanistic-Empirical Pavement Design Guide (MEPDG) input sensitivities across the entire problem domain for continuously reinforced concrete pavement (CRCP). Hamzah et al (2015b) used RSM to determine the effects of aging on the rheological properties of asphalt binders.…”
Section: Introductionmentioning
confidence: 99%
“…Kavussi et al (2014) utilized RSM to evaluate the effects of aggregate gradation, hydrated lime and Sasobit content on the indirect tensile strength of warm mix asphalt. Ceylan et al (2014) employed RSM to model the Global Sensitivity Analyses (GSA) results for evaluation of Mechanistic-Empirical Pavement Design Guide (MEPDG) input sensitivities across the entire problem domain for continuously reinforced concrete pavement (CRCP). Hamzah et al (2015b) used RSM to determine the effects of aging on the rheological properties of asphalt binders.…”
Section: Introductionmentioning
confidence: 99%
“…ated the sensitivity of MEPDG performance predictions to traffic, material, and other design input parameters, but few comprehensive sensitivity studies of the effects of climate on performance predictions have been performed (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Nearly all sensitivity analyses of MEPDG performance predictions to climate inputs to date have simply compared results using one weather station to results using another (15,16).…”
mentioning
confidence: 99%
“…In another study, Taflanidis et al (2011) constructed response surface model with moving least squares method to perform sensitivity analysis to determine the influence of input variables on the outcome variable for the robust design of offshore energy conversion devices . Recently, Ceylan et al (2014) constructed response surface models by multivariate linear regressions and artificial neural networks (ANN) to perform sensitivity analysis for robust design of concrete pavement design, and the authors concluded that ANN is a robust and accurate method to capture the nonlinearities between variables. However, for our datasets, ANN did not perform well in our initial investigations; hence, we exclude the ANN method from this paper.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, the time is limited for design engineers to make decisions about design variables and design concepts. One way to solve this problem is to use response surface models-they are also known as surrogate models and metamodels-for sensitivity analysis (Ceylan et al 2014;Chen et al 2006;Ma et al 2015;Sathyanarayanamurthy and Chinnam 2009;Taflanidis et al 2011). The sensitivity analysis-based response surface models allow for efficient studies of how uncertainties in input variables affect system performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation